Fresno County DSS Director Ben Kelley Retirement Dinner at Holiday Inn - Watkins, Howard::::::::: (1989)
Ben Kelley receiving framed State Assembly Resolution from Cruz Bustamante and Ken Maddy representatives ? And ?; Don Hogner seated